Segmental allotetraploidy generates extensive homoeologous expression rewiring and phenotypic diversity at the population level in rice. Issue 20 (16th September 2017) - Sun, Yue; Wu, Ying; Yang, Chunwu; Sun, Shuai; Lin, Xiuyun; Liu, Lixia; Xu, Chunming; Wendel, Jonathan F.; Gong, Lei; Liu, Bao
Abstract: Allopolyploidization, that is, concomitant merging and doubling of two or more divergent genomes in a common nucleus/cytoplasm, is known to instantly alter genomewide transcriptome dynamics, a phenomenon referred to as "transcriptomic shock." However, the immediate effects of transcriptomic alteration in generating phenotypic diversity at the population level remain underinvestigated. Here, we employed the MassARRAY‐based Sequenom platform to assess and compare orthologous, allelic and homoeologous gene expression status in two tissues (leaf and root) of a set of randomly chosen individuals from populations of parental rice subspecies ( indica and japonica ), in vitro "hybrids" (parental mixes), reciprocal F1 hybrids and reciprocal tetraploids at the 5th‐selfed generation (S5). We show that hybridization and whole genome duplication (WGD) have opposing effects on allelic and homoeologous expression in the F1 hybrids and tetraploids, respectively. Whereas hybridization exerts strong attenuating effects on allelic expression differences in diploid hybrids, WGD augments the intrinsic parental differences and generates extensive and variable homoeolog content which triggers diversification in expression patterning among the tetraploid plants. Coupled with the vast phenotypic diversity observed among the tetraploid individuals, our results provide experimental evidence in support of the notion that allopolyploidy catalyses rapid phenotypic diversification in higher plants. Our data further suggest that largely stochastic homoeolog content reshuffling rather than alteration in total expression level may be an important feature of evolution in young segmental allopolyploids, which underlies rapid expression diversity at the population level.